Experimental Study on Combustion Characteristics of Biodiesel–Ethanol Dual Fuel: An Overview - Tai, Mai; Vo, Chau; Duong, Long; Do, Am; Huynh, Vang; Nguyen, Huong (Journal of Technical Education Science, 2023)
Biodiesel and bioethanol are two renewable fuels available on the market, both of which have been used on internal combustion engines as an additive as they have physicochemical properties similar to commercial petroleum fuels. However, different properties of biodiesel and ethanol in terms of viscosity and energy density directly affect the combustion process of internal combustion engines. This article aims to analyze and evaluate the influence of 100% blended biofuels including biodiesel-ethanol on combustion characteristics and emissions under diesel engine conditions, as well as the status of biodiesel-ethanol fuel use, a recommended orientation for the development of adaptive diesel engine in the future at Vietnam. These studies on the influence of biodiesel-ethanol fuels blend were carried out on the optical research engine system (constant volume combustion chamber) and the actual engine testing. The results revealed that change in the concentration of ethanol affects the physicochemical properties of BE fuels blend, and using more ethanol in the mixture causes more effect on the trend of combustion characteristics and emissions. Consequently, it is possible to use a 100% biodiesel-ethanol blend on conventional diesel engines with little modifications.